52.0k views
5 votes
If f(x)= 2x^5-3x^3+2x^2+1, then f(1)=?
A. -1
B. 0
C. 1
D. 2
E. 4

User Xbb
by
5.6k points

2 Answers

4 votes

Problem:


\tt{if \: \: f(x) = 2 {x}^(5) - 3{x}^(3) + 2 {x}^(2) + 1 \: \: then \: \: f(1) = ?}

Let's try!


\quad \quad \quad \quad \tt{f(x) = 2 {x}^(5) - 3 {x}^(3) + 2 {x}^(2) + 1}


\quad \quad \quad \quad \tt{f(x) = 2 {(1)}^(5) - 3 {(1)}^(3) + 2 {(1)}^(2) + 1}


\quad \quad \quad \quad \tt{f(x) = 2 (1) - 3 (1) + 2 (1) + 1}


\quad \quad \quad \quad \tt{f(x) = 2 - 3 + 2 + 1}


\quad \quad \quad \quad \tt{f(x) = 2 - 3 +3}


\quad \quad \quad \quad \tt{f(x) = 2 \: \: \cancel{ \color{red}- 3 +3}}


\quad \quad \quad \quad \tt{f(x) = 2 }

Hence, The answer is:


\quad \quad \quad \quad \huge\boxed{\tt{ \color{green}f(x) = 2 }}

________

#LetsStudy

If f(x)= 2x^5-3x^3+2x^2+1, then f(1)=? A. -1 B. 0 C. 1 D. 2 E. 4-example-1
User Wottensprels
by
4.9k points
3 votes

Answer:

2

Explanation:

f(x)= 2x^5-3x^3+2x^2+1

Let x=1

f(1)= 2(1)^5-3(1)^3+2(1)^2+1

= 2*1 -3*1+2(1) +1

= 2-3+2+1

2

User JosefN
by
5.5k points